Pengaruh Kompetensi SDM, Moralitas dan Sistem Pengendalian Internal Terhadap Pencegahan Fraud Dalam Pengelolaan Keuangan Desa - Santi Putri Laksmi, Putu; Sujana, I Ketut (E-Jurnal Akuntansi, 2019)
This research was conducted at 27 Service Villages in Denpasar City using a total method or census. The respondents used were 97 people consisting of the Village Head, Village Secretary, Treasurer and Village Consultative Body (BPD). The data analysis technique used is multiple linear regression analysis. The results of this study indicate that the competence of human resources has a positive effect on prevention of fraud in village financial management. Morality has a positive effect on prevention of fraud in managing village finances. The internal control system has a positive effect on preventing fraud in managing village finances. This means, with the competency of human resources, good morality and a strong internal control system, it can prevent fraud in managing village finances. Keywords : Human resource competency, morality, control system, internal, fraud